Penerapan sanksi hukum dan regulasi dalam mengurangi kecelakaan lalu lintas - Rifka Safira; Rahmiati; Rahmad Sujud Hidayat; Lala (JURNAL EKONOMI, BISNIS DAN HUMANIORA, 2023)
Implementing laws and regulations in reducing traffic accidents is a crucial step in improving road safety. Traffic accidents have a serious impact on society and the country's economy. Implementation of laws and regulations includes safety standards, rule enforcement, deterrent and deterrent effects, public education, and regular evaluation. This helps create a safer traffic environment and reduces the potential for accidents. However, implementing laws and regulations is only one part of a comprehensive traffic safety solution. Support from other efforts such as improving road infrastructure and quality driving education is needed. The importance of implementing laws and regulations is also in reducing the social, economic and environmental impacts of traffic accidents. Therefore, continuous efforts to improve the effectiveness of laws and regulations and public awareness of the importance of road safety are essential to create a safer and better traffic environment for everyone. Suggestions involve strengthening law enforcement, traffic safety education, regulatory evaluation, stakeholder cooperation, and improving safe road infrastructure. Further research is also needed to develop more effective strategies for improving traffic safety. By implementing these suggestions, it is hoped that traffic accidents can be minimized, and people can feel safer when carrying out activities on the road.